ANALISIS PENERAPAN STANDAR AKUNTASI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA TOKO KAIN AQSHA DI KECAMATAN SANGATTA UTARA - Fajar Iqmal; Nuuridha Matiin; Nanok Fitriyadi (Tinta Nusantara 2018 Vol.1, 2020)
The purpose of this study was to determine whether the application of accounting at the aqsa cloth shop in the North Sangatta district was in accordance with the financial accounting standards of entities without public accountability (SAK ETAP). This research is quantitative reserch. With the data used in the study, namely the documentation of the financial statements of the Aqsa Fabric Shop. The results of the research at the Aqsa Fabric Shop show that the financial statements used still use simple financial statements by only recording cash in and cash out. There are still many errors in the recording. Therefore, the Aqsa Fabric Shop is still not in accordance with SAK ETAP